Enhancing Collaborative Learning in Wikis through an Iterative Model by Supporting Various User Roles - Shah, Asad Ali; Ravana, Sri Devi (Malaysian Journal of Computer Science, 2014)
Web 2.0 paved the way for Computer-Supported Collaborative Learning (CSCL) using Wikis. However, basic Wikis have limited features in terms of catering for various roles and responsibilities of users causing hindrance for effective collaborative work among them. Hence, it is important to investigate how these varying roles can band together in a CSCL environment.This research recommends an iterative model with defined users and roles working in a collaborative environment. The study underwent a 3-week exercise, involving 16 participants belonging to the Bachelor of Information Technology program at a university in Malaysia. Data collected from these participants helped in evaluating the model proposed. Data collection techniques involved structured surveys and structured interviews to understand participants’ perceptions during collaborative work (group assignment).The results gathered from the surveys were statistically tested using the non-parametric statistical test named “Wilcoxon signed-rank test”.The proposed iterative model encouraged the students to be more active and responsible in the CSCL environment. Studyshowed that the inclusion of users and their roles helped in managing and performing group tasks. The research identified lists of users and roles working within the CSCL environment. The iterative model supported theseusers and roles, monitoring their progress using process checks.